Inoculum and disease dynamics of circular leaf spot of persimmon caused by Mycosphaerella nawae under semi-arid conditions - Vicent, Antonio; Bassimba, Daniel; Hinarejos, Concha; Mira, José L. (2017)
The epidemiology of circular leaf spot of persimmon, caused by Mycosphaerella nawae, was studied in a semi-arid area in Spain for two consecutive years. No conidia were observed on diseased leaves and all infections were thought to be caused by ascospores formed in the leaf litter. Ascospores were released mainly in April and May, but relatively low numbers in June were able to induce severe symptoms on trap plants. Temperature was not significantly correlated with ascospore catches or disease incidence on trap plants, indicating that it was not a limiting factor for disease development during the period of study. Rainfall was above normal, but still considerably lower than in endemic areas of Korea. Most infections coincided with rains, but the disease was observed also on trap plants exposed to less than 1 mm of precipitation and even in the absence of rain. Orchards were flood irrigated once inoculum deposits in the leaf litter had already been depleted, so it was not possible to determine its effects on ascospore release and disease development. The use of a wind tunnel to determine inoculum production allowed detection of physiologically mature ascospores of M. nawae in the leaf litter 1-2 weeks before they were released to air in the orchard. Disease progress was fitted to the monomolecular growth curve, associated with monocyclic pathogens and diseases with a variable incubation period as a function of the host phenology.